Supervising academic: Cyprus Youth for the Sustainable Development Goals - Souleles, Nicos (My University, 2026)
YOU NEVER TOLD US! Social awareness campaign about Sustainable Development Goals among young people in Cyprus. A collaborative group project by final year undergraduate students at Cyprus University of Technology, Autumn 2024.